Otorhinolaryngological diseases of Geriatric visiting Tertiary Care Hospital in Nepal: An Overview of neglected and underrated field - Malla, Neeta Shakya; Shrestha, Supri Raj; Shah, Deepa (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: In Nepal, person aged 60 years and above is considered elderly. The population of Nepal is approximately 30 million, and people aged 60 years and above makes about one tenth of the total population. This study aims to report the main complaints and prevalence of otorhinolaryngological diseases in patients aged 60 years and above, who visited outpatient otolaryngology department of Manmohan Memorial College and Teaching Hospital, Kathmandu, Nepal during study period. Material and Methods: It is a prospective descriptive cross-sectional study done in Manmohan Memorial College and Teaching Hospital, Kathmandu, Nepal for the duration of a year. All patients aged 60 years and above attending to Ear, Nose and throat (ENT) Outpatient Department were included in the study. The information including demographic data, ENT Complaints and physical examination were noted. Analysis of data was done and report was prepared. Results: Total of six hundred and ninety three patients were enrolled over the period of one year for the study. Number of Male and female patients in the study were almost equal. The otological problems had the highest prevalence constituting 51.7% of the study population. More than Twenty eight (28.3 %) percent had oral and oropharyngeal pathologies. Nasal complaints constituted 10.8% of the study population and 9.2% had pathologies related to neck and others. Conclusion: Hearing loss is the most common diagnosis among all the otological pathologies and epistaxis the most common nasal problem. Head and Neck malignancy is also increasing among the geriatric population.